+0  
 
0
803
6
avatar+2533 

                                                                  

 Mar 21, 2016

Best Answer 

 #2
avatar+116126 
+10

a(x - y)  = b(y - x)

 

ax - ay  = by - bx

 

ax + bx  = ay + by

 

x(a + b)  = y(a + b)

 

x / y  =  (a + b) / (a + b)    =  1

 

 

 

cool cool cool

 Mar 21, 2016
 #1
avatar+561 
+10

Apply algebra and play with it for a bit.

\(a(x-y)=b(y-x) \)

\(ax-ay=by-bx\)

\(ax+bx=by+ay\)

\(x(a+b)=y(a+b)\)

\(x=y\frac{a+b}{a+b}\)

\(x=y\)

Therefore,

\(\frac{x}{y}=1\)

 Mar 21, 2016
 #2
avatar+116126 
+10
Best Answer

a(x - y)  = b(y - x)

 

ax - ay  = by - bx

 

ax + bx  = ay + by

 

x(a + b)  = y(a + b)

 

x / y  =  (a + b) / (a + b)    =  1

 

 

 

cool cool cool

CPhill Mar 21, 2016
 #3
avatar+2533 
0

Thanks CPhill and Will85237

 Mar 21, 2016
 #4
avatar+116126 
0

OK, Solveit....although, technically.....Will beat me to it....!!!!!!

 

 

 

cool cool cool

 Mar 21, 2016
 #5
avatar+2533 
0

i don t understand, what do you mean :)

Solveit  Mar 21, 2016

30 Online Users

avatar
avatar
avatar